2013
DOI: 10.1007/s00038-013-0465-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of heat warning systems: systematic review of epidemiological evidence

Abstract: Research in this area is limited. Prospective designs applying health behavior theories should establish whether HWS can produce the health benefits they are purported to achieve by identifying the target vulnerable groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 64 publications
0
130
0
2
Order By: Relevance
“…Reflecting the tradition of systematic reviews in the health sciences, health-related adaptation was the focus of six articles (Walker et al 2011;Hosking and Campbell-Lendrum 2012;Bouzid et al 2013;Cheng and Berry 2013;Poutiainen et al 2013;Toloo et al 2013). The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
See 3 more Smart Citations
“…Reflecting the tradition of systematic reviews in the health sciences, health-related adaptation was the focus of six articles (Walker et al 2011;Hosking and Campbell-Lendrum 2012;Bouzid et al 2013;Cheng and Berry 2013;Poutiainen et al 2013;Toloo et al 2013). The most dominant adaptation focus within which systematic reviews have penetrated has been reviewing lessons from, and trends in, adaptation governance (Hardee and Mutunga 2010;Berrang-Ford et al 2011;Ford et al 2011;Pearce et al 2011;Ford et al 2012a, b;Larsen et al 2012;Murtinho and Hayes 2012;Biesbroek et al 2013;Kamau and Mwaura 2013;Vink et al 2013).…”
Section: Systematic Review For Adaptation Research: Challenges and Comentioning
confidence: 99%
“…Consideration of context, processes, and mechanisms of causality may require more time commitment per document than extraction of key estimates or discrete items of information. Many realist or in-depth reviews, for example, are conducted using fewer than 50 articles, often 30-40 documents (Bouzid et al 2013;Cheng and Berry 2013;Kajan and Saarinen 2013;Linnenluecke et al 2013), and even in-depth qualitative systematic analyses with as few as 15-20 articles (Walker et al 2011;Toloo et al 2013). Research has shown that systematic review of complex and heterogeneous literature bases cannot rely solely on strict keyword searches (Greenhalgh and Peacock 2005), and this is likely to apply to many complex adaptation policy and practice questions.…”
Section: Literature and Information Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…These include, but are not limited to, early warning systems, hotlines providing heat-related health information, ensuring organizations working with vulnerable groups have protocols and plans in place to manage risks during a heatwave and providing outreach to homeless people. 2,[22][23][24][25][26][27][28] These strategies support measures taken by individuals and communities to manage health impacts of heat such as drinking plenty of water, minimizing physical activity, checking on vulnerable family members or friends, spending time in cool spaces such as shopping centers or cinemas, planning activities so to avoid being outdoors during the hottest parts of the day, taking cool showers or baths, and keeping homes as cool as possible. 26 Moreover, local governments can target community-level intervention, including awareness campaigns reinforcing messages set out by state governments and NGOs, distribute health information in different languages and assist in the identification of local risks that can guide the development of local plans.…”
Section: Heatwave Managementmentioning
confidence: 99%